ANTIMICROBIAL PRESCRIPTION PRACTICES AMONG THE INPATIENTS OF E. N. T DEPARTMENT USING WHO AWARE CLASSIFICATION: A CROSS-SECTIONAL STUDY - KUMAR, K. G. SATHEESH; BHARATHI, UPPU; MEENAKSHI, L.; LATHA, M. ASHA (International Journal of Current Pharmaceutical Research, 2026)
Objective: To collect antimicrobial prescriptions of patients admitted to the E. N. T ward. To analyze the collected antimicrobial prescriptions of E. N. T inpatients based on the WHO AWaRe classification. Methods: An observational cross-sectional study was conducted in the Department of E. N. T at a tertiary care hospital in Tirupati, Andhra Pradesh, from January to June 2025, after obtaining approval from the Institutional Ethics Committee. All inpatient prescriptions containing at least one antibiotic, irrespective of age, gender, or indication, were included. Written informed consent was obtained from adult participants, and assent from parents for minors. The original prescriptions were returned after documentation, and photocopies or photographs were analyzed. Antibiotics were classified according to the WHO AWaRe classification (2023), and WHO core prescribing indicators were applied to assess rational drug use. Results: Out of 310 prescriptions analyzed, Amoxyclav (82.58%) from the Access group was most frequently prescribed, followed by Watch group antibiotics-Ceftriaxone (13.55%) and Cefixime (3.87%). No Reserve antibiotics were used. The average number of drugs per encounter was 5.13, and 100% of prescriptions contained antibiotics. Injections were used in 86.4%, 97% of drugs were from the Essential Medicine List, and 100% were prescribed by generic name. Conclusion: The predominance of Access group antibiotics indicates partial adherence to WHO guidelines; however, polypharmacy and high antibiotic use highlight the need to strengthen antimicrobial stewardship in the E. N. T department.